The Potential of “GENIUS”: Deep Learning Integrated Application to Fight Obesity - Rahadi, Putu Nindya Krisnadewi; Raharja, Ananda Eka; Haidir, Andi Ahmad (Universitas Multimedia Nusantara, 2024)
Lifestyle changes regarding food consumption and sedentary lifestyle has led to increase prevalence of obesity worldwide, including in Indonesia. Obesity as a risk factor for various diseases has become an urgent issue considering that currently available therapies have not shown optimal results in overcoming this problem. The